Antiviral effect of dehydroepiandrosterone on Japanese encephalitis virus infection - Chang, Chia-Che; Ou, Yen-Chuan; Raung, Shue-Ling; Chen, Chun-Jung (Journal of General Virology, 2005)
Japanese encephalitis virus (JEV), which causes neurological disorders, completes its life cycle and triggers apoptotic cell death in infected cells. Dehydroepiandrosterone (DHEA), an adrenal-derived steroid, has been implicated in protection against neurotoxicity and protection of animals from viral-induced encephalitis, resulting in an increased survival rate of the animals. Currently, the mechanisms underlying the beneficial effects of DHEA against the virus are largely unknown. In this study, DHEA suppression of JEV replication and virus-induced apoptosis in murine neuroblastoma (N18) cells was investigated. It was found that DHEA suppressed JEV-induced cytopathic effects, JEV-induced apoptotic cell death and JEV propagation in a concentration-dependent manner. Antiviral activity was more efficient in cultures treated with DHEA immediately after viral adsorption compared with that in cultures receiving delayed administration after adsorption or transient exposure before adsorption. JEV-induced cytotoxicity was accompanied by the inactivation of extracellular signal-regulated protein kinase (ERK). Inactivation of ERK by JEV infection was reversed by DHEA. When cells were treated with the ERK inhibitor U0126, DHEA lost its antiviral effect. Activation of ERK by anisomycin mimicked the action of DHEA in suppressing JEV-induced cytotoxicity. DHEA-related compounds, such as its sulfate ester (DHEAS) and pregnenolone, were unable to suppress JEV-induced cytotoxicity and ERK inactivation. The hormone-receptor antagonists ICI 182780 and flutamide failed to abrogate the antiviral effect of DHEA. These findings suggest that the antiviral effect of DHEA is not linked directly to the genomic steroid-receptor pathways and suggest that the signalling pathways of ERK play a role in the antiviral action of DHEA.